A Rare Case of Ataxia Telangiectasia in Malaysia - Ashari, Noor Suryani Mohd; Hamid, Wan Zuraida Wan Abdul (Bangladesh Journal of Medical Science, 2017)
Ataxia telangiectasia is a primary immunodeficiency disease that affects multiple organs systems. Affected patients typically manifest ataxia, immune function abnormalities, sinopulmonary infections, and telangiectasia. Ataxia telangiectasia is listed as a rare disease by the Office of Rare Diseases [ORD] of the National Institutes of Health [NIH]. Because ataxia telangiectasia is so rare, doctors may not be familiar with the symptoms, or methods of making a diagnosis. Not all children develop in the same manner or at the same rate; it may be some years before ataxia telangiectasia is properly diagnosed. We report a rare case of ataxia telangiectasia in Malaysia who was diagnosed only at the age of 10 years. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.154-156